Development of limit state design method for Malaysian bolted timber joints - Jumaat, Mohd Zamin; Razali, Fadini Mohamad; Rahim, Ahmad Hazim Abdul (2008)
The existing procedure for designing bolted timber joints in Malaysia is still based on the working stress design method (WSDM), in accordance with the MS 544: Part 5:2001. Timber design standards in most developed countries presently have been revised to incorporate the limit state design method (LSDM). This paper outlines a study, which is being carried out to propose a procedure for adopting the LSDM in the next revision of the Malaysian Standard. The embedment test parallel to the grain in accordance with the BS EN 383:1993 was carried out for three bolt sizes and five species of Malaysian timbers from various densities. The results were found to be similar to the values for hardwoods that are suggested in Eurocode 5. Joint tests on double shear bolted joint parallel to the grain were also carried out to determine the ultimate capacities of the joints. The ultimate loads obtained from the experimental works were then compared to the European Yield Load (EYM).